Policy Innovation of Coretax in the Modernization of the Tax Administration System: A Case Study at KPP Pratama Bandung Cicadas - Farhan Rivaldy Mudzakir (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research examines policy innovation in the implementation of the Coretax system as part of the modernization of the tax administration system in Indonesia, especially at KPP Pratama Bandung Cicadas. Coretax is an integrated information technology-based system, designed to unify all tax administration processes such as NPWP registration, Annual Tax Return reporting, payment, and tax invoice management in one efficient digital platform. This research approach uses qualitative methods with data collection techniques through in-depth interviews with tax officials, documentation, and field observations. The results showed that the Coretax system provides easy access, service efficiency, and transparency in the implementation of tax obligations, although it is still faced with technical challenges and user adaptation, especially among taxpayers who are not familiar with digital technology. The findings also show a decrease in the number of new taxpayer registrations at the beginning of the implementation in 2025, which is influenced by the transition period, lack of socialization, and the process of adapting to new technology. This study recommends increasing digital education, providing technical assistance, continuous monitoring, and inclusive policies to support the success of Coretax's overall implementation in the long term.